2005
DOI: 10.1148/radiol.2353040601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endocardial Trabeculae on Left Ventricular Measurements and Measurement Reproducibility at Cardiovascular MR Imaging

Abstract: Trabeculae significantly affect quantifications of LV volume and mass. The superior reproducibility of LV measurements with the inclusion of endocardial trabeculae in the cavity volume favors this tracing algorithm for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
6
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 15 publications
(10 reference statements)
8
159
6
3
Order By: Relevance
“…Despite observations of Papavassilliu et al .,10 who concluded that the difference between these two methods resulted in a change in estimated volume and mass, there were no data in medical literature about the influence of trabecular relief in the hypothetical geometrical shape of ventricular chamber.…”
Section: Discussionmentioning
confidence: 97%
“…Despite observations of Papavassilliu et al .,10 who concluded that the difference between these two methods resulted in a change in estimated volume and mass, there were no data in medical literature about the influence of trabecular relief in the hypothetical geometrical shape of ventricular chamber.…”
Section: Discussionmentioning
confidence: 97%
“…It appears that in end-systole, intertrabecular space may not be completely obliterated, as is supported by both contrast echocardiography and MRI studies. 19,26 In one contrast echocardiography study, LV end-diastolic volume showed a larger increase than LV end-systolic volume, with a resulting increase in ejection fraction. 17 In this study, however, the amount of ultrasound contrast material that was injected was very small, which might have aggravated the effects of ultrasound contrast destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary muscles and trabeculations were excluded from the calculated LV mass. 12 The density of myocardial tissue was set at 1.05 g/mL. Of note, LV masses analyzed by the steady state free precision method tend to be Ϸ15% lower than masses recorded by the turbo gradient echo method.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%